Knowledge in your classroom: A model of analysis for specialization codes in classroom discourse - Vidal Lizama, Margarita (Onomázein, 2017)
The paper proposes a model of analysis of specialization codes in classroom discourse. This model aims to explore the nature of the knowledge being construed in the interaction between teacher and student in the classroom. The model offered emerges from the study of teaching practices in popular education in Chile. The model integrates two theoretical bod-ies: Legitimation Code Theory for understanding the organizing principles of knowledge and Systemic Functional Linguistics for exploring the meaning resources construing knowledge in classroom discourse.